Correlation of Visuospatial Ability and EEG Slowing in Patients with Parkinson’s Disease - Dominique Eichelberger; Pasquale Calabrese; Antonia Meyer; Menorca Chaturvedi; Florian Hatz; Peter Fuhr; Ute Gschwandtner (Parkinson's Disease)
Background. Visuospatial dysfunction is among the first cognitive symptoms in Parkinson’s disease (PD) and is often predictive for PD-dementia. Furthermore, cognitive status in PD-patients correlates with quantitative EEG. This cross-sectional study aimed to investigate the correlation between EEG slowing and visuospatial ability in nondemented PD-patients. Methods. Fifty-seven nondemented PD-patients (17 females/40 males) were evaluated with a comprehensive neuropsychological test battery and a high-resolution 256-channel EEG was recorded. A median split was performed for each cognitive test dividing the patients sample into either a normal or lower performance group. The electrodes were split into five areas: frontal, central, temporal, parietal, and occipital. A linear mixed effects model (LME) was used for correlational analyses and to control for confounding factors. Results. Subsequently, for the lower performance, LME analysis showed a significant positive correlation between ROCF score and parietal alpha/theta ratio (b=.59, p=.012) and occipital alpha/theta ratio (b=0.50, p=.030). No correlations were found in the group of patients with normal visuospatial abilities. Conclusion. We conclude that a reduction of the parietal alpha/theta ratio is related to visuospatial impairments in PD-patients. These findings indicate that visuospatial impairment in PD-patients could be influenced by parietal dysfunction.